2005
DOI: 10.1007/s00381-005-1190-9
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of craniopharyngiomas

Abstract: Craniopharyngiomas are benign, epithelial neoplasms of the sella and parasellar region seen in children and adults that may arise from neoplastic transformation of ectoderm-derived epithelial cell remnants of Rathke's pouch and the craniopharyngeal duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 20 publications
1
61
0
4
Order By: Relevance
“…2 The tumor exhibits solid and cystic components and is thought to originate from rests of cells arising from the lumen of the craniopharyngeal duct, the precursor of the adenohypophysis. 3 Of particular interest to ophthalmologist is the locally aggressive behavior of craniopharyngiomas, causing compression of visual structures, in addition to pituitary and hypothalamic dysfunction and hydrocephalus in as many as 58% of pediatric cases.…”
Section: Introductionmentioning
confidence: 99%
“…2 The tumor exhibits solid and cystic components and is thought to originate from rests of cells arising from the lumen of the craniopharyngeal duct, the precursor of the adenohypophysis. 3 Of particular interest to ophthalmologist is the locally aggressive behavior of craniopharyngiomas, causing compression of visual structures, in addition to pituitary and hypothalamic dysfunction and hydrocephalus in as many as 58% of pediatric cases.…”
Section: Introductionmentioning
confidence: 99%
“…6,15,18,19,23 Normally, the pituitary gland is formed by fusion of the ectoderm of the oral cavity stomodeum with the neuroectoderm of the diencephalon during the 3rd and 4th weeks of gestation. This fusion of the stomode- um and neuroectoderm gives rise to the adenohypophysis and neurohypophysis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that craniopharyngioma accounts for 1.2-4% of all primary intracranial tumors and 5-10% of primary brain tumors in children [1]. It originates from the third ventricle-hypothalamus -funnel-pituitary axis [2]. Based on its histological origin, craniopharyngioma often occurs in the sella region while its clinical symptoms are usually manifested as visual disturbances and endocrine disorders [3].…”
Section: Introductionmentioning
confidence: 99%